2021
DOI: 10.3390/cells10020270
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of B Cells in Atherosclerosis

Abstract: Atherosclerosis is a lipid-driven inflammatory disease of blood vessels, and both innate and adaptive immune responses are involved in its development. The impact of B cells on atherosclerosis has been demonstrated in numerous studies and B cells have been found in close proximity to atherosclerotic plaques in humans and mice. B cells exert both atheroprotective and pro-atherogenic functions, which have been associated with their B cell subset attribution. While B1 cells and marginal zone B cells are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 204 publications
(308 reference statements)
1
34
0
Order By: Relevance
“…B cells have three main effects: the production of antibody, the presentation of antigen or T cell interaction, and the release of cell factor. It was reported that all of the effect can regulate atherosclerosis and were associated with the activation status of the B cells, 17 which was consistent with the enhanced expression of B cells in patients with dyslipidemia observed in our experiment. Other experimental data indicated that changes in cellular lipid metabolism may have critical effects on humoral and cellular immunity, especially T cells and T cell subsets proliferation and cell fate decisions.…”
Section: Discussionsupporting
confidence: 92%
“…B cells have three main effects: the production of antibody, the presentation of antigen or T cell interaction, and the release of cell factor. It was reported that all of the effect can regulate atherosclerosis and were associated with the activation status of the B cells, 17 which was consistent with the enhanced expression of B cells in patients with dyslipidemia observed in our experiment. Other experimental data indicated that changes in cellular lipid metabolism may have critical effects on humoral and cellular immunity, especially T cells and T cell subsets proliferation and cell fate decisions.…”
Section: Discussionsupporting
confidence: 92%
“…It is well described that an imbalance of B cell homeostasis can cause devastating effects and tissue injury. 10,13,33,34 The hyperactivated and dysfunctional B cell state together with an exaggerated antibody production in hypercholesterolemic mice lacking functional GPR55 signaling fits well to the proatherogenic phenotype. [35][36][37][38] B cell maturation and activation is precisely controlled by multiple factors, but begins with the binding of B-cell receptor (BCR) to a specific antigen, 39 such as an OSE.…”
Section: Discussionmentioning
confidence: 71%
“…10 Under hypercholesterolemic conditions, B cells may become hyperactivated with deregulation of plasma cell formation, thereby promoting atherosclerosis. 10,13 GPR55 is a G protein-coupled orphan receptor expressed by various leukocyte subsets, including B and T cells, but also natural killer cells, monocytes, macrophages, and neutrophils. According to murine immune cell transcriptomic data (Immgen.org), 14 GPR55 is highly expressed by splenic plasma cells (PC) and, to a lower extent, MZ B cells.…”
Section: Role Of B Cell Gpr55 In Atherosclerosismentioning
confidence: 99%
“…It has also recently been reported that MZB cells have thermal protective activity. Using a genetic model of MZB cell deficiency, it has been shown that the role of MZB in the negative regulation of proatherogenic TFH cells, via the PDL1 (programmed cell death ligand 1) axis, programmes cell death 1 [89]. Before this, it was assumed that a potential atheroprotective role might appear through the secretion of OSE-specific antibodies.…”
Section: Modulating B-cell Receptor Signalingmentioning
confidence: 99%